ChemInform Abstract: Recent Developments in the Chemistry of Thiourea Oxides. Issue 5 (February 2015) - Makarov, Sergei V.; Horvath, Attila K.; Silaghi‐Dumitrescu, Radu; Gao, Qingyu
Abstract Review: [83 refs.